Trends in International Funding for Financial Inclusion - Dashi, Edlira; Lahaye, Estelle; Rizvanolli, Ralitsa (World Bank, Washington, DC, 2014)
In recent years, the development community has sustained support for microfinance but broadened funding to encompass a wider goal of financial inclusion. International funders have been adapting priorities to meet this broader vision, as reflected in the 2012 consultative group to assist the poorest (CGAP) funder survey. This brief analyzes trends in the international funding landscape for financial inclusion.